Identical Parallel Machine Scheduling Using Genetic Algorithm To Minimize Total Tardiness For Cnc 4 Axis In Pt Dirgantara Indonesia (persero) - Muflih Hafidz Danurhadi; Dida Diah Damayanti; Widia Juliani (eProceedings of Engineering, 2019)
Abstract in manufacturing operations, fulfilling the demand by the due dates is one way to keep customer satisfaction level. if the demand was delivered after the due dates, the tardiness penalty was occurred due to maintain the customer satisfaction level. scheduling was needed to reduce the tardiness that may occur in manufacturing operations. the production scheduling system in part fabrication is considered parallel machine scheduling due to several machine with same capabilities and characteristic. thus in order to get optimal solution to reduce tardiness, this research used genetic algorithm. keyword: parallel machine, scheduling, tardiness, genetic algorithm